ANALYSIS OF THE INFLUENCE OF THE ENVIRONMENT AND SATISFACTION ON PRODUCT TRUST FOR GREEN PRODUCTS (CONSUMERS OF THE BODY SHOP COSMETICS IN THE PEKANBARU AREA) - Isma Juliana; Tetti Ayunita; Sinta Deviana Br. Siregar (Yayasan Wayan Marwan Pulungan, 2025)
This research aims to analyze the influence of the environment and satisfaction on product trust, especially for green products. This work uses quantitative methods to find model correlations using statistics. The results of this research show that: (1) The influence of environmental friendliness has a positive and significant effect on green satisfaction; (2) environmental friendliness has a positive and significant effect on green trust. (3) green satisfaction has a positive and significant effect on green trust..